Development of a Community-Learning-Center Management System for Local Administrative Organizations in Samut Prakan Province - Prathumrat, Chirasak; Boonumpai , Tipkesorn; Hoksuwan, Pongprasert (Dusit Thani College Journal, 2020)
This study aimed to propose the development of a community-learning-center-management system for local administrative organizations in Samut Prakan province. This research focused on R & D. The research sample was 19 staff members at a community learning center who provided information on current conditions where they work and regarding the need for such a management system. The focus-group technique was employed by nine specialists in supervisory-system management. Five qualified raters also examined and approved the development of a community-learning-center-management system for local administrative organizations. The research tool used for data collection was document analysis. Data collection using the focus-group technique and evaluation were qualitatively verified by using inferential analysis. Quantitative data were presented in terms of frequency, percentage, mean, and standard deviation. The study results indicate that 1) A community learning-center-management system for local administrative organizations in Samut Prakan province consists of input factors including content, knowledge, service, personnel, budget, premises, materials, equipment, media, technology, cooperative networks, and factors / support. This is a process-management system with CLCM-APOSCARE. It involved: (1) A-Analysis (2) P-Planning (3) O-Organizing (4) S-Staffing (5) C-Coordinating (6) A-Allocating (7) R-Reporting and (8) E-Evaluating elements. The results also revealed that 2) The experts supported the conclusion that a community-learning-center management system will give the operations a high level of suitability. Such a system will offer very useful strategies to be used in administrative operations in the province.